A CONTENT ANALYSIS ON THE FEATURE OF VOCABULARY IN “GROW WITH ENGLISH HANDBOOK” - airin malau; ira sinaga; rinita simamora (English Language Teaching Prima Journal (ELT), 2025)
This investigation seeks to identify and scrutinize the typologies of vocabulary exercises incorporated within the